2021
DOI: 10.3390/cancers13194935
|View full text |Cite
|
Sign up to set email alerts
|

Maraviroc Prevents HCC Development by Suppressing Macrophages and the Liver Progenitor Cell Response in a Murine Chronic Liver Disease Model

Abstract: Maraviroc (MVC), a CCR5 antagonist, reduces liver fibrosis, injury and tumour burden in mice fed a hepatocarcinogenic diet, suggesting it has potential as a cancer therapeutic. We investigated the effect of MVC on liver progenitor cells (LPCs) and macrophages as both have a role in hepatocarcinogenesis. Mice were fed the hepatocarcinogenic choline-deficient, ethionine-supplemented diet (CDE) ± MVC, and immunohistochemistry, RNA and protein expression were used to determine LPC and macrophage abundance, migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Further, the autosomal recessive deficiencies of CCR5 underlie resistance to HIV-1 [ 22 ]. Maraviroc, a CCR5 antagonist, reduces liver fibrosis and injury, chronic liver disease, and tumor burden in mice fed a hepatocarcinogenic diet [ 23 ]. Another recent study demonstrated that CCR5 expression in adipose tissue and peripheral blood mononuclear cells was significantly higher in women with PCOS compared with women in the control group [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the autosomal recessive deficiencies of CCR5 underlie resistance to HIV-1 [ 22 ]. Maraviroc, a CCR5 antagonist, reduces liver fibrosis and injury, chronic liver disease, and tumor burden in mice fed a hepatocarcinogenic diet [ 23 ]. Another recent study demonstrated that CCR5 expression in adipose tissue and peripheral blood mononuclear cells was significantly higher in women with PCOS compared with women in the control group [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral drugs may have an inhibitory effect on the entire replication cycle. They can be classified according to the stage to which they are targeted: cell entry inhibitors [52][53][54][55][56][57], replicant inhibitors [40,[58][59][60][61][62][63][64] and assembly, maturation, and release inhibitors [65][66][67][68][69]. Within a therapeutic class, antiviral agents can have different effects.…”
Section: Different Types Of Antiviralsmentioning
confidence: 99%
“…There are different types of inhibitors. Maraviroc inhibits HIV entry by binding selectively and specifically to the CCR5 receptor on the CD4 cell surface [52]. Enfuvirtide is a synthetic peptide that blocks the HIV envelope from fusing with the CD4 cell membrane [53].…”
Section: Cell Entry Inhibitorsmentioning
confidence: 99%
“…CCL5 has also been linked to excess ECM deposition (Passman et al ., 2021; Bonnard et al ., 2022). Brain ECM exists in diffuse and condensed forms and both types can restrict neuroplasticity (Miyata & Kitagawa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, our aim was to explore the possibility that CCL5 and other potential ECM effectors that limit pyramidal arbor, gamma power and SWR abundance may be elevated in APOE4 human and TR mice. We also investigated the possibility that reductions in CCR5, a molecule linked to excess ECM deposition in other end organs as well as reduced plasticity in the brain (Passman et al ., 2021; Bonnard et al ., 2022; Shen et al ., 2022), might rescue biochemical, neurophysiological and/or behavioral alterations associated with this allele.…”
Section: Introductionmentioning
confidence: 99%